Marcadores genéticos, antropometria e qualidades físicas básicas nos estágios maturacionais de nadadores paraibanos - Costa, Adalberto Veronese da (2008)
The aim of this research was to analyse genetic markers, anthropometry and basic physical qualities in the differret stages of sexual maturation in swimmers in Paraíba. It is characterised as a descriptive cross sectional study. The sample was composed of 119 swimmers (males) that were divided among the stages of sexual maturation, from 7 to 17,9 years of age. They were associated to a local federation, the Confederação Brasileira de Desportes Aquáticos. The tests used were: genetic markers dermatoglyphics; Anthropometry body mass, stature, arm span, fat percentage and somatotype; physical qualities speed tests (25 meters crawl), strength (vertical jump) to inferior limbs, verarm throwing arremesso of a 2kg medicineball to superior limbs and abdominal), resistence (12 minutes to swimming), agility (he multistage 20-meter shuttle run test), flexibility (sit and reach test ) and coodination (stroke index); power of swimming (mean velocity in 25 meters mutiplied by body mass) and the self assessment of the sexual maturation supervised by a pediatric specialist. In the analyses we used the test normality of Shapiro-Wilk, then, we used ANOVA- one way followed by Post-Hoc test of Scheffé. The data showed in dermatogliphics a genetic tendence to velocity (L>W) with a predominance of the meso-ectomorphic somatotype profile; in relation to the physical qualities there was an evolution of the results in every stage due to the antropometric variables, except in the coordination tests. There were no significative differences between the stages. We conclude that swimming in Paraíba is composed of a signicative number of velocists with a mesomorph somatotype profile and low fat percentage, and that made it posssible to us to recomend that the trainings must be individual and according to personal characteristics of each athlete, and that the used variables must be specific for every region of the country. This dissertation presents a relation of multidiciplinar interface and its content has an application in Physical Education and Medicine